Stochastic Analysis on Efficiency Vaccination in a SIR Model - Granados, Carlos (2025)
In this paper, we model the stochastic effect of vaccination on an epidemic which like epimdemic model, it can be susceptible to environmental changes. This study is carried out using a SIR model in which population remain susceptible after having been vaccinated. One important point of our research is that we apply a whit noise on recuperate rate of the infected individuals. Further, we show some stability results and some numerical simulations.